Modified Impression Technique of a Custom Made Hand Painted Iris For an Ocular Prosthesis: A Case Report - Nusima Mohamed; Muhammad Amin Azahar (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Indexed by Scopus/MyCite